Repentance for the Holocaust : Lessons from Jewish Thought for Confronting the German Past - Chung, C. K. Martin (Book collections on Project MUSE., 2017)
"Develops the biblical idea of "turning" (tshuvah) into a conceptual framework to analyze a particular area of contemporary German history, commonly referred to as Vergangenheitsbewältigung or "coming to terms with the past." Chung examines a selection of German responses to the Nazi past, their interaction with the victims' responses, such as those from Jewish individuals, and their correspondence with biblical repentance. In demonstrating the victims' influence on German responses, Chung asserts that the phenomenon of Vergangenheitsbewältigung can best be understood in a relational, rather than a national, paradigm"--